[PP.37.09] IMPACT OF INFLAMMATOIRY CYTOKINES ON AORTIC STIFFNESS IN PATIENTS WITH CHRONIC KIDNEY DISEASE. (September 2016) - Desjardins, M.P.; Fortier, C.; De Serres, S.; Lariviere, R.; Agharazii, M.
Abstract : Objective: Cardiovascular diseases are the primary cause of morbidity and mortality in patients with chronic kidney disease (CKD). Aortic stiffness is a non-traditional risk factor in these patients. Using an animal model of CKD with vascular calcification, we reported that inflammation is involved in the development of aortic calcification and stiffness. Hence, increased vascular production of IL-1, IL-6 and TNF was associated with aortic calcification. Therefore, we investigated the impact of the latter cytokines on aortic stiffness and determined the profile of inflammatory cytokines in a cohort of CKD patients. Design and method: This is a transversal study involving 196 CKD patients on dialysis, in which aortic stiffness was determined non-invasively by the assessment of carotid-femoral pulse wave velocity (cf-PWV). The profile of inflammatory cytokines (IFN, IL-1, IL-1, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12 and TNF) was determined in plasma by ELISA using a Multiplex. Results: Mean cf-PWV of the cohort was 12.8 ± 3.9 m/s. Median plasma levels of IL-1, IL-6 and TNF were 1.01 pg/ml, 4.26 pg/ml and 3.33 pg/ml, respectively. IL-6 levels positively correlated with cf-PWV (= 0.218, P = 0.006, R = 0.129), suggesting a role in aortic stiffness. In contrast, no correlation between PWV and plasma levels of IL-1 or TNF was established. Conclusions: This study reveals a relationship between an inflammatory cytokine, Il-6, and aortic stiffness in patients with CKD. Our results, together with our previous findings in an experimental animal model, indicate that IL-6 may represent a novel therapeutic target of cardiovascular diseases in CKD.